Ruthenium(II)-catalyzed switchable C3-alkylation versus alkenylation with acrylates of 2-pyridylbenzofurans via C-H bond activation - Kommagalla, Yadagiri; Mullapudi, Venkanna Babu; Francis, Fredi; Ramana, Chepuri V. (Catalysis Science & Technology, 2015)
We documented an interesting observation of ruthenium (II)-catalyzed benzofuran C-H activation and subsequent functionalization with acrylates that reveals that a simple base can switch the process from alkylation to alkenylation.

Total synthesis of (+)-petromyroxol - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The total synthesis of (+)-petromyroxol establishing its absolute configuration has been accomplished. The strategy developed employs easily accessible carbohydrate building blocks and comprises flexible and scalable chemistry that allowed the synthesis of (+)-petromyroxol along with its three diastereomers varying the stereochemistry mainly at C5 and/or C6. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Glucose diacetonide; Petromyroxol; Pheromone; Sea Lamprey; Total synthesis

Fluoride-mediated dephosphonylation of α-diazo-β-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkanna Babu; Wakchaure, Vivek Chandrakant; Ramana, Chepuri V. (Organic Letters, 2016)
The possibility of fluoride-mediated selective dephosphonylation of α-diazo-β-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting α-diazocarbonyl intermediates undergo a (3 + 2)-cycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess α-diazo-β-carbonyl phosphonates) or Michael addition (with conjugated olefins).

Total synthesis and structural assignment of hexaketide xylarinolb and its C1-epimer - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Asian Journal of Organic Chemistry, 2016)
The total synthesis of two isomeric hexaketides isolated along with sordarial, which have the proposed relative arabino and ribo configurations, has been executed. A Rh-catalyzed [2+2+2]-alkyne cyclotrimerization has been employed as the key reaction to construct the central dihydroisobenzofuran core. The absolute configuration of the xylarinolB hexaketide has been established as l-arabino. This is the first natural product of this family for which the absolute configuration has been determined, and this can be extended to provide structural details of several of related hexaketides.
Keywords: hexaketides; sordarial; Wilkinson's catalyst; xylarinolB; {[2+2+2]-cyclotrimerization